Prinsen og det halve kongerige. En beretning fra det inkaiske landskab - Raahauge, Kirsten Marie (Tidsskriftet Antropologi, 2019)
This article is formed as a narrative interpretation of the dramatic conflict which took place between the two royal brothers Huascar and Atahuallpa, both Incas of Tawantinsuyu, ‘the unit of the four regions’, the Indian name for ‘the Inca empire’. The article is also an unfurling of a formal-structural figure in Incaic perception and categorization, namely the division into two halves, also to be found in certain terms of the guec/iua-language of the Incas. The analysis further treats the play between the two halves - when it concems towns: moieties - and the entirety, as well as the relationship between this structure and the conception of the Incaic landscape as space. The key in this interpretation is the Incaic categorization of the landscape as structured through the figure pairs of two halves which on a higher level are interconnected in an entirety. These two halves are supported by various pairs of metaphors implying either symmetry or asymmetry between the two positions. It is argued that this categorization was crucial for the structural relations that defined the positions of the brothers Huascar and Atahuallpa and eventually for the fali of Tawantinsuyu.